PHYTOCHEMICAL PROFILING AND ANTIBACTERIAL EFFICACY SCREENING OF AGLAIA MALABARICA SASIDH - Ravindran, Archana Elamkulam; Thoppil, John Ernest (International Journal of Current Pharmaceutical Research, 2018)
Objective: Aglaia malabarica is an unexplored endemic forest tree belonging to the family Meliaceae. The present study was conducted to screen the phytochemical constituents of the leaf extract, to analyze the important secondary metabolites and to determine the antibacterial efficacy of the plant extract. Methods: Antibacterial activity was studied using agar based disc diffusion method. Four strains of bacteria were used for the antibacterial study that includes Staphylococcus aureus, Pseudomonas aeruginosae, Proteus vulgaris and Bacillus megaterium. Results: The presence of constituents like, carbohydrates, proteins, tannins, phenols, terpenoids, flavonoids, alkaloids and steroids were confirmed. Saponin was found to be absent. The secondary metabolites quantified were terpenoids, phenols and flavanoids, which were found in considerable amounts. The minimum inhibitory concentration (MIC) of all the bacteria studied was found to be 500 Âµg methanolic leaf extract. Conclusion: The plant extract was found to be highly potent against both the Gram positive and Gram negative strains and this property may be attributed to the potent phytochemicals revealed in the extract.